Visual impairment and social isolation, depression and life satisfaction among older adults in Ghana: analysis of the WHO's Study on global AGEing and adult health (SAGE) Wave 2. Issue 1 (29th June 2020) - Tetteh, John; Fordjour, Gladys; Ekem-Ferguson, George; Yawson, Anita Ohenewa; Boima, Vincent; Entsuah-Mensah, Kow; Biritwum, Richard; Essuman, Akye; Mensah, George; Yawson, Alfred Edwin
Abstract : Aim: To estimate the prevalence of visual impairment (VI) and associated factors and further quantify its association with social isolation, depression and life satisfaction among older adults in Ghana. Methods: WHO Study on Global AGEing and Adult Health Ghana dataset for older adults 50 years and above was used for this study. Social isolation, depression and life satisfaction were our primary outcomes with VI being our secondary outcome. We employed negative binomial, Poisson and generalised negative binomial regression models individually modified with Coarsened Exact Matching method of analysis. All analysis was performed by adopting robust SE estimation using Stata V.15. Results: The prevalence of VI was 17.1% (95% CI14.3 to 20.2) and the factors associated include age groups, educational level, religion, region, where the participant was born, and difficulty in work/households activity (p<0.05). The inferential analysis shows that the significant log-likelihood score of social isolation and life satisfaction for older adults with VI was 0.25 more (95% CI 0.03 to 0.47) and 0.04 less (95% CI −0.08 to −0.01), respectively, compared with those without VI. The prevalence of depression among older adults with VI was significantly 90% higher compared with non-VI (adjusted prevalence ratio (95% CI) = 1.90 (1.17 to 3.09), p<0.001). Conclusion: The prevalence of VI is associated with increasing age, educational level and self-rated health. VI was identified to be associated with social isolation, depression and diminishing life satisfaction. In order to achieve sustainable development goal #3, a national focus on geriatric care as part of the implementation of the National Ageing Policy will garner improvement in the quality of life of older adults with visual VI in Ghana. Eye health practitioners at all levels of the health systems should consider the psychosocial consequences of VI for the optimum care of the older adult client.